The representation of extremists in Western media - Kapelari, Laura (My University, 2015)
As radicalised Muslim converts gain ever greater attention within the War on Terror (WoT) and the media, an investigation into their portrayal and the associated discourses becomes ever more relevant. This study aims to shed more light on the representation of these extremist individuals in the Western media, specifically white converts to Islam who become radicalised, exploring whether there is indeed a difference between the portrayal of female and male extremists, at the same time seeking to reveal any related social or national anxieties. The findings indicate that there is indeed a difference: while women extremists are stripped bare of all political agency, the men, though exposed to rhetoric condemning their treachery as well as often depicted as capitulating to mental illness, remain largely intact as agents. This comes down to men being located in the international sphere, while women are fixed within the domestic equivalent. In terms of the link to social and national anxieties, it becomes evident that not only has the domestic fear surrounding the “homogenous Islamist terrorist enemy” (Samiei 2010, 1149) led to the terrorist (and by extension the white Muslim convert) being equated with the foreigner, but that as a result, terrorism/extremism and immigration have come to be situated within the same framework, where the slippery slopes of counter-terrorism and anti-immigration meld together.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Arts in International Relations University of the Witwatersrand 2015
Keywords: Extremists; Democracy; Terrorism; Government policy; United States